PENGARUH RADIASI DAN LOKASI TUMBUH TERHADAP PERTUMBUHAN DAN PENYAKIT HAWAR DAUN TALAS kv KETAN - L Agus Sukamto; Saefudin Saefudin (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Taro (Colocasia esculenta (L.) Schott) is an important tuber crop, grown widely in humid tropics and a source of carbohydrate for many people in Asia, Africa, and the Pacific islands. The leaves and stalks of taro are used as vegetable, as they contain a high protein that is useful for people diet in developing countries. Taro is underutilized plant that has potency as an alternative food.Plant propagation of taro is usually done by using its rhizome or stolon so that the genetic diversity is very limited. In vitro and irradiated techniques can increase its genetic diversity and multiply the plant that has superior quality and quantity.Taro